The expectant brain–pregnancy leads to changes in brain morphology in the early postpartum period. (24th December 2021) - Chechko, Natalia; Dukart, Jürgen; Tchaikovski, Svetlana; Enzensberger, Christian; Neuner, Irene; Stickel, Susanne
Abstract: There is growing evidence that pregnancy may have a significant impact on the maternal brain, causing changes in its structure. To investigate the patterns of these changes, we compared nulliparous women ( n = 40) with a group of primiparous women ( n = 40) and multiparous mothers ( n = 37) within 1–4 days postpartum, using voxel-based and surface-based morphometry (SBM). Compared with the nulliparous women, the young mothers showed decreases in gray matter volume in the bilateral hippocampus/amygdala, the orbitofrontal/subgenual prefrontal area, the right superior temporal gyrus and insula, and the cerebellum. These pregnancy-related changes in brain structure did not predict the quality of mother–infant attachment at either 3 or 12 weeks postpartum nor were they more pronounced among the multiparous women. SBM analyses showed significant cortical thinning especially in the frontal and parietal cortices, with the parietal cortical thinning likely potentiated by multiple pregnancies. We conclude that, compared with the brain of nulliparous women, the maternal brain shows widespread morphological changes shortly after childbirth. Also, the experience of pregnancy alone may not be the underlying cause of the adaptations for mothering. As regards the exact biological function of the changes in brain morphology, longitudinal research will be needed to draw any definitive conclusions.